Safety Distance of Shotcrete Subjected to Blasting Vibration in Large-Span High-Speed Railway Tunnels - Ao Li; Dingli Zhang; Qian Fang; Jiwei Luo; Liqiang Cao; Zhenyu Sun (Shock and Vibration)
The drill and blast method is widely used in constructing tunnels in rock. Unfortunately, blasting vibration can damage newly performed shotcrete layers which are major support structures to stabilize surrounding structures. Therefore, investigation of the influence of blasting on shotcrete and determining reasonable distance between blasting work face and shotcrete position is of great importance. In this paper, a large-span tunnel excavated by drill and blast method acting as a high-speed railway station has been investigated. Blast vibration in the tunnel was recorded using microseismic monitoring technique. Empirical prediction equations for peak particle velocity (PPV) were obtained through regression analysis based on the obtained monitoring data. The attenuation law of tensile stress imposed on shotcrete layer due to blasting and bond strength of shotcrete-rock interface was also investigated. Minimum safety distance between shotcrete and blasting positions was calculated based on bond failure criterion. Evolution law considering different factors including blasting charge, rock mass class, and setting time of shotcrete was also obtained, which could be applied to determine blast charge shotcrete arrangements for tunnel constructions in future. The obtained results showed that the safety of shotcrete could be ensured and shotcrete falling off the rock could be prevented under current blast constructions.